2021
DOI: 10.1111/sms.13979
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of strain‐induced impairments of patellar tendon micromorphology in adolescent athletes

Abstract: High‐level patellar tendon strain may cause impairments of the tendon's micromorphological integrity in growing athletes and increase the risk for tendinopathy. This study investigated if an evidence‐based tendon exercise intervention prevents high‐level patellar tendon strain, impairments of micromorphology and pain in adolescent basketball players (male, 13–15 years). At three time points over a season (M1‐3), tendon mechanical properties were measured using ultrasound and dynamometry, proximal tendon microm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 39 publications
4
23
1
2
Order By: Relevance
“…As the tendon cannot be trained in isolation, the high-loading protocol also leads to adaptations in muscle strength. Plantar flexor MVC increased by 7.2% from PRE to POST in the High-load group, which corresponds to gains to the same high-loading protocol in healthy populations who trained at home with the mobile device (10%, [ 31 ]) or under laboratory conditions on a dynamometer (7%, [ 46 ]). The aforementioned structural adaptations of the Achilles tendon have not been affected or biased by a possible correlation between the leg laterality of the injured leg and the leg laterality of the dominant leg.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As the tendon cannot be trained in isolation, the high-loading protocol also leads to adaptations in muscle strength. Plantar flexor MVC increased by 7.2% from PRE to POST in the High-load group, which corresponds to gains to the same high-loading protocol in healthy populations who trained at home with the mobile device (10%, [ 31 ]) or under laboratory conditions on a dynamometer (7%, [ 46 ]). The aforementioned structural adaptations of the Achilles tendon have not been affected or biased by a possible correlation between the leg laterality of the injured leg and the leg laterality of the dominant leg.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, to counteract phases of enhanced injury risk, a specific tendon training based on the most effective mechanical stimulus should improve the structural integrity of the tendon and thereby reducing injury prevalence. Indeed, high-loading exercise decreased the prevalence of tendon pain in adolescent handball and basketball players [ 30 , 31 ]. Taking the aforementioned into consideration, it seems reasonable to assume that tendinopathy patients in which the tendons tissue integrity has deteriorated may also benefit from high-loading interventions on a structural and clinical level.…”
Section: Introductionmentioning
confidence: 99%
“…These adaptations alter the mechanical function of the tendon, as a stiffer tendon experiences less strain at a given load and stores more energy at a given strain, and a stronger tendon resists a greater external load prior to failure. Stiffer lower limb tendons are associated with greater rates of force development [11][12][13][14], faster sprint times [15], improved running economy [5,16,17], and reduced risk of tendon damage [18]. Although there is some evidence that strain magnitude and duration are important factors [19][20][21], the mechanical loading stimulus across other loading dimensions (e.g., loading volume, rate, duty cycle) required to induce anabolic tendon adaptation is unclear.…”
Section: Key Pointsmentioning
confidence: 99%
“…Although there is in general a strong association between muscle strength and tendon stiffness, 6 during the last years, studies on adult, 3 adolescent, 4,[10][11][12] and preadolescent athletes 13 reported imbalances in the development of muscle strength and tendon stiffness, leading to increased tendon strain during maximum effort muscle contractions. One consequence of increased tendon strain may be structural impairments within the tendon tissue.…”
Section: Introductionmentioning
confidence: 99%
“…16 In addition, recent studies from our group provided evidence for an association between high patellar tendon strain levels and a deterioration of the micromorphological structure of the proximal part of the patellar tendon in adolescent athletes. 12,17 Thereby, athletes suffering from tendinopathy and asymptomatic athletes developing tendinopathy demonstrated higher tendon strain and a more disorganized microstructure of the tendon. 17 This supports the idea that tendon strain is an important mechanical factor for tendon damage and overuse.…”
Section: Introductionmentioning
confidence: 99%